PROTECTION MEASURES FOR VARIOUS CONSTRUCTIONS ON THE TERRITORY OF DILIJAN INTERNATIONAL SCHOOL FROM GROUNDWATER IMPOUNDMENT (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
The article substantiates the use of subsurface drainage of horizontal ring type to protect the bases of various kinds of structures in the territory of Dilijan International School against impoundment of groundwaters. As a result of analytical calculations, providing the hydrogeological conditions of the object, all the relevant parameters of the drainage system have been identified. These parameters correspond to the building regulations, requirements for the construction of ground structures and underground utilities that would be constructed on the site of the school, and will be protected from groundwater impoundment for the entire period of their operation.
Keywords: groundwater impoundment; horizontal ring type drainage